Effect of Trichoderma harzianum and Some Selected Soil Amendment Against Damping off Disease Complex of Potato and Chilli - Uddin, MM; Akhtar, N; Islam, MT; Faruq, AN (The Agriculturists, 2012)
Soil applications with poultry refuse, cocodust, vermicompost, ash, sawdust, khudepana, cowdung, solarized sand, Trichoderma harzianum and or with seed treatment by T. harzianum were evaluated against damping off disease complex of potato and chilli. All the treatments significantly reduced percent damping off over control. T. harzianum treated seed along with soil treatment with T. harzianum performed best in terms of seed germination, percent damping off reduction and enhanced growth characters than soil application with T. harzianum alone. The experiment indicates that seed treated with T. harzianum then sown in different soil amendment applied seed bed performed better in all parameters than only application with soil amendment. Among the different soil amendments, poultry refuse and vermicompost have promising impact on seed germination, reduction of percent damping off and growth of potato and chilli seedlings when applying along with T. harzianum. Keywords: Damping off; potato; chilli; Trichoderma harzianum; soil amendment DOI: http://dx.doi.org/10.3329/agric.v9i1-2.9485 The Agriculturists 2011; 9(1&2): 106-116